Effectifiveness of Behavioral Counseling with Modeling Techniques Improv Students Vocability to Be A Trough Leader Lesson Study in Singaraja - Kadek Budi Aryanto; Iketut Dharsana; I Wayan Tirka (International Conference on Technology and Educational Science)
This study aims to determine the effectiveness of Cognitive Behavioral counseling in leadership abilities in the group cognitive behavioral counseling theory with modeling techniques to improve student behavior . The research was conducted using a sample of 20 students taken from 32 students. Data collection in this study uses a questionnaire. Then the results of the questionnaire were analyzed based on product moment formula and t - test and can be concluded that tcount = 7.862 > ttable = 2.02, that Ho is rejected and Ha is accepted. It was concluded that there was effectiveness in cognitive behavioral counseling using modeling techniques in improving the behavior of students receiving advice from others